2015
DOI: 10.1007/s15010-015-0788-4
|View full text |Cite
|
Sign up to set email alerts
|

Raoultella planticola peritonitis in a patient on continuous ambulatory peritoneal dialysis

Abstract: A 65-year-old man on continuous ambulatory peritoneal dialysis was admitted with peritonitis. Empirical antibiotic therapy was initiated, and Raoultella planticola was identified in the peritoneal fluid culture. We treated the patient with intraperitoneally administered ciprofloxacin and ceftazidime according to the antibiotic susceptibility. His condition improved, and he was well treated with a 2-week antibiotic course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
13
0
2
Order By: Relevance
“…It is an emerging pathogen, associated most commonly with urinary tract infections and bacteraemia. There has been only one previous report of R. planticola PD peritonitis worldwide …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is an emerging pathogen, associated most commonly with urinary tract infections and bacteraemia. There has been only one previous report of R. planticola PD peritonitis worldwide …”
mentioning
confidence: 99%
“…Treatment failure with intraperitoneal cephazolin and ceftazidime, despite the isolate displaying in‐vitro susceptibility to these antimicrobials, has been described in an immunocompetent patient . Recovery occured only after the administration of intraperitoneal ciprofloxacin.…”
mentioning
confidence: 99%
“…Los principales factores de riesgo para desarrollar infección por R. planticola son: las neoplasias primarias o metastásicas (principalmente con compromiso de la vía biliar); el trauma o alguna intervención reciente y el trasplante de médula ósea (7)(8)(9). En el caso de nuestra paciente las manifestaciones clínicas fueron un cuadro agudo de síndrome febril con escalofríos, dolor abdominal y deposiciones blandas.…”
Section: Discussionunclassified
“… 3 - 6 Although R. planticola is an environmental bacterium found in the water, soil, and plants, it is also isolated from nearly all human tissues and fluids. 7 - 8 After its identification, the clinical significance of R. planticola remained uncharacterized for almost a decade. 8 However, since the description of the case of septicemia reported by Freney et al 9 in 1984 (identified as Klebsiella trevisanii at the time), many other cases of infections in humans have been reported; therefore the pathogenicity of R. planticola needs to be revised.…”
Section: Discussionmentioning
confidence: 99%
“…The infection by this emerging pathogen is associated with either immunosuppression states, such as neoplasia, chronic renal disease, and diabetes mellitus, or invasive procedures and trauma. 7 , 10 The infection sites reported so far that are caused by R. planticola are: (i) sepsis/bacteremia; 9 , 11 - 17 (ii) pneumonia; 14 - 18 (iii) abdominal infections; 8 , 10 - 12 , 19 - 21 (iv) urinary tract; 22 , 23 (v) skin and soft tissues; 24 - 26 and (vi) conjunctivitis, 27 which account for a little more than 20 cases.…”
Section: Discussionmentioning
confidence: 99%